Ontologi Ekonomi Islam Ibn Khaldun: Sebuah Pendekatan Holistik - Amirullah, Mulia; Rohman, Pupun Saepul (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2024)
Ibn Khaldun’s Islamic economic ontology integrates material, spiritual, individual, and social aspects. Emphasizing justice, sustainability, and ethical production, it offers a holistic framework for a fair, prosperous, and sustainable economy. From material perspectives, it highlights economic blessings and justice, linking production and consumption to these principles. Wealth distribution through zakat and equitable distribution fosters social stability, while agricultural development ensures economic self-reliance. Sustainable resource management underscores environmental preservation. Spiritually, moral values like justice and honesty underpin Islamic economics, reflected in fair income distribution, exemplified by zakat.Activities rooted in spiritual values aim for harmony between humans and God, enhancing well-being. Individually, intellect is key to understanding Sharia laws and economic responsibilities. Research and experimentation foster knowledge, supporting sustainable economic development. Socially, equitable income distribution is vital for societal welfare, requiring government, entrepreneurial, and community participation. Overall, Ibn Khaldun’s economic ontology lays the groundwork for a productive, just, sustainable economy aligned with human values.